2019
DOI: 10.1029/2018ja025949
|View full text |Cite
|
Sign up to set email alerts
|

Generic Magnetic Field Intensity Profiles of Interplanetary Coronal Mass Ejections at Mercury, Venus, and Earth From Superposed Epoch Analyses

Abstract: We study interplanetary coronal mass ejections (ICMEs) measured by probes at different heliocentric distances (0.3–1 AU) to investigate the propagation of ICMEs in the inner heliosphere and determine how the generic features of ICMEs change with heliospheric distance. Using data from the MErcury Surface, Space ENvironment, GEochemistry, and Ranging (MESSENGER), Venus Express and ACE spacecraft, we analyze with the superposed epoch technique the profiles of ICME substructures, namely, the sheath and the magneti… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

25
105
2

Year Published

2019
2019
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 83 publications
(134 citation statements)
references
References 74 publications
25
105
2
Order By: Relevance
“…However, the ratio of the maximum magnetic field intensity measured in the sheath to that of the ejecta remained relatively constant throughout, which is consistent with Janvier et al (2019). We observed on average the maximum magnetic field strength in the ejecta to decrease by a factor of ∼3.4 from MESSENGER to Venus Express and ∼2 from Venus Express to near 1 AU.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…However, the ratio of the maximum magnetic field intensity measured in the sheath to that of the ejecta remained relatively constant throughout, which is consistent with Janvier et al (2019). We observed on average the maximum magnetic field strength in the ejecta to decrease by a factor of ∼3.4 from MESSENGER to Venus Express and ∼2 from Venus Express to near 1 AU.…”
Section: Discussionsupporting
confidence: 89%
“…However, except for a few studies that used multipoint spacecraft observations (Burlaga et al, 1981;Cane et al, 1997;Farrugia et al, 2011;Good et al, 2015Good et al, , 2018Janvier et al, 2019;Kilpua et al, 2011;Möstl, 2015;Möstl et al, 2009;Prise et al, 2015;Wang et al, 2018;Winslow et al, 2016Winslow et al, , 2018, CME measurements are largely restricted to single-point observations in space (see also discussion in Lugaz et al, 2018). However, except for a few studies that used multipoint spacecraft observations (Burlaga et al, 1981;Cane et al, 1997;Farrugia et al, 2011;Good et al, 2015Good et al, , 2018Janvier et al, 2019;Kilpua et al, 2011;Möstl, 2015;Möstl et al, 2009;Prise et al, 2015;Wang et al, 2018;Winslow et al, 2016Winslow et al, , 2018, CME measurements are largely restricted to single-point observations in space (see also discussion in Lugaz et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This finding supports the case for an upstream space weather monitor sitting on or near the Sun‐Earth line: The first‐order flux rope structure observed at such a monitor (and the normalized B z component of that structure) is likely to be the same as that arriving subsequently at the Earth, even in cases where the radial separation distance between the monitor and Earth is large (e.g., Event 8). With an estimation of how the field magnitude profile also evolves (as recently considered by Janvier et al, ), simple and accurate B z forecasting with a near‐Sun upstream monitor may be possible. However, differences due, for example, to a change in rope orientation may be difficult to predict without global modeling.…”
Section: Discussionmentioning
confidence: 99%
“…Janvier et al (2019) studied the average sheath duration increase from Mercury to Venus and Earth's orbits and found that the typical sheath duration increases by a factor of 5 from Mercury to Earth and the ratio of sheath to ME durations doubles between these two locations. Janvier et al (2019) studied the average sheath duration increase from Mercury to Venus and Earth's orbits and found that the typical sheath duration increases by a factor of 5 from Mercury to Earth and the ratio of sheath to ME durations doubles between these two locations.…”
Section: Cme Sheathmentioning
confidence: 99%